Numerical simulation of alternating current linear sweep voltammetry at microdisc electrodes - Gavaghan, D; Elton, D; Bond, A (2001)
We extend our earlier work on the numerical simulation of ac linear sweep voltammetry at macroelectrodes to the case of microdisc electrodes. This requires the solution of the underlying diffusional transport equations in two dimensions, rather than one, using a cylindrical coordinate system. We use the two-dimensional FIRM algorithm combined with a specially designed exponentially expanding mesh. We examine the ac response as a function of the frequency and amplitude of the ac signal, and as a function of the non-dimensional parameter p = (nFa2v/RTD)1/2, where a is electrode radius, v the sweep rate, and D the diffusion coefficient. Results are analysed using Fast Fourier Transform (FFT) methods. We are able to derive a range of conditions under which radial diffusion has only a minor effect on the ac response of the system. The analytical results available for macroelectrodes therefore carry through to the microelectrode case for many practical ranges of system parameters (electrode size, dc sweep rate and diffusion coefficient). Experimental results are given which show good agreement with the numerical simulations.